Potential of a Cetuximab‐based radioimmunotherapy combined with external irradiation manifests in a 3‐D cell assay. Issue 4 (11th February 2014) - Ingargiola, M.; Runge, R.; Heldt, J.‐M.; Freudenberg, R.; Steinbach, J.; Cordes, N.; Baumann, M.; Kotzerke, J.; Brockhoff, G.; Kunz‐Schughart, L.A.
<x xml:space="preserve">Abstract</x> Targeting epidermal growth factor receptor (EGFR)‐overexpressing tumors with radiolabeled anti‐EGFR antibodies is a promising strategy for combination with external radiotherapy. In this study, we evaluated the potential of external plus internal irradiation by [90Y]Y‐CHX‐A″‐DTPA‐C225 (Y‐90‐C225) in a 3‐D environment using FaDu and SAS head and neck squamous cell carcinoma (HNSCC) spheroid models and clinically relevant endpoints such as spheroid control probability (SCP) and spheroid control dose 50% (SCD50, external irradiation dose inducing 50% loss of spheroid regrowth). Spheroids were cultured using a standardized platform. Therapy response after treatment with C225, CHX‐A″‐DTPA‐C225 (DTPA‐C225), [90Y]Y‐CHX‐A″‐DTPA (Y‐90‐DTPA) and Y‐90‐C225 alone or in combination with X‐ray was evaluated by long‐term monitoring (60 days) of spheroid integrity and volume growth. Penetration kinetics into spheroids and EGFR binding capacities on spheroid cells were identical for unconjugated C225 and Y‐90‐C225. Spheroid‐associated radioactivity upon exposure to the antibody‐free control conjugate Y‐90‐DTPA was negligible. Determination of the SCD50 demonstrated higher intrinsic radiosensitivity of FaDu as compared with SAS spheroids. Treatment with unconjugated C225 alone did not affect spheroid growth and cell viability. Also, C225 treatment after external irradiation showed no additive effect. However, the combination of external irradiation with Y‐90‐C225 (1 µg/ml, 24 hr) resulted in a considerable benefit as reflected by a pronounced reduction of the SCD50 from 16 Gy to 9 Gy for SAS spheroids and a complete loss of regrowth for FaDu spheroids due to the pronounced accumulation of internal dose caused by the continuous exposure to cell‐bound radionuclide upon Y‐90‐C225‐EGFR interaction.